A kind of biomimetic graft polyethylene and its preparation method and application, modified asphalt

CN122832153APending Publication Date: 2026-09-29HEBEI UNIV OF ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611251586.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-18
Publication Date
2026-09-29

AI Technical Summary

Technical Problem

现有研究主要通过马来酸酐接枝、橡胶复配及纳米材料协同改性方法改善PE改性沥青性能,但仍存在界面作用弱、改性效果有限等问题

Benefits of technology

本发明采用聚多巴胺(PDA)与硅烷偶联剂对聚乙烯进行仿生协同接枝改性,经PDA与硅烷偶联剂仿生接枝处理后,PE表面由平整光滑转为粗糙蓬松,并伴随明显颗粒状附着结构,同时,表面引入N-H、Si-O活性官能团。与普通PE相比,仿生接枝PE具有更强的表面极性,其与沥青间的溶解度参数差值减小、结合能增大,两者相容性明显改善。从分子作用机理分析,多巴胺首先通过氧化自聚合在PE表面形成PDA初始层,随后硅烷偶联剂水解生成的硅醇基团与PDA发生脱水缩合反应,而其另一端的活性有机官能团增强了其与沥青组分之间的界面作用,从而构建稳定的界面连接结构。此外,仿生接枝PE改性沥青表现出更优异的高温抗变形性能、抗疲劳性能及低温抗裂性。且本发明的制备方法操作简单,适于实现工业化应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122832153A_ABST
    Figure CN122832153A_ABST
Patent Text Reader

Abstract

The application provides a kind of biomimetic grafting polyethylene and its preparation method and application, modified asphalt, belong to functional material technical field.The PE of the present application is oxidized, and the obtained oxidized PE, hydrochloric acid dopamine neutralization buffer solution is mixed to carry out biomimicry, the obtained PDA biomimetic PE, silane coupling agent and solvent are mixed to carry out grafting reaction, and the biomimetic grafting polyethylene is obtained.The present application adopts PDA and silane coupling agent to carry out biomimetic grafting modification on PE, and the biomimetic grafting polyethylene has stronger surface polarity, and the solubility parameter difference between the asphalt is reduced, the binding energy is increased, and the compatibility of the two is obviously improved.Dopamine is first self-polymerized on the surface of PE to form PDA initial layer by oxidation, then the silanol group generated by the hydrolysis of silane coupling agent and PDA occurs dehydration condensation reaction, and the active organic functional group at the other end enhances the interface interaction between it and asphalt components, thereby constructing stable interface connection structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of functional materials technology, and in particular to a biomimetic grafted polyethylene, its preparation method and application, and modified asphalt. Background Technology

[0002] Among various types of industrial solid waste, waste plastics, often referred to as "white pollution," have long been a global technological challenge for recycling. Applying waste plastics to road engineering is one effective way to solve the problem of large-scale waste accumulation. Existing research shows that the application of waste plastics in road engineering can not only achieve resource recycling and promote the resource utilization of bulk solid waste, but also improve the road performance of asphalt pavements. Waste plastics have a complex composition, including polyethylene (PE), polyvinyl chloride (PVC), and polypropylene (PP), among other components, with waste PE accounting for more than 20.6% of the total.

[0003] Although PE-modified asphalt exhibits good high-temperature stability and fatigue resistance, the modification effect of PE-modified asphalt alone is limited. Existing technologies combine PE with other materials or perform graft activation treatment to improve the compatibility between PE and the asphalt matrix. For example, using maleic anhydride to graft PE-modified asphalt significantly improves the high-temperature performance of the modified asphalt. Adding PE to asphalt binders in combination with nano-clay increases the dispersion of PE in the asphalt matrix, thereby improving the storage stability of the modified asphalt. Adding transpolymerized tendonamine (TPOR) and crosslinking additives to PE addresses the problem of poor storage stability in PE-modified asphalt, thus improving its storage stability and rheological properties. A rubber / plastic composite high-viscosity modified asphalt (RPRA) was prepared using waste rubber and waste PE. It was found that rubber and plastic tend to exhibit uneven distribution and block agglomeration in the fluorescent phase of the matrix asphalt, while polyethylene wax helps to uniformly disperse the modifier, thereby enhancing the network structure and improving the compatibility of the modified asphalt. Existing research mainly improves the properties of PE-modified asphalt through maleic anhydride grafting, rubber compounding, and synergistic modification with nanomaterials. However, problems such as weak interfacial interactions and limited modification effects still exist. Therefore, how to construct a functional layer with high reactivity and strong interfacial adhesion on the PE surface and further enhance the interfacial polarity between PE and asphalt is a key issue in improving the stability of PE-modified asphalt systems. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a biomimetic grafted polyethylene, its preparation method and application, and modified asphalt. This invention utilizes a biomimetic grafting modification method of PE using PDA and a silane coupling agent to construct a "PE-PDA-silane coupling agent-Asphalt" dual-interface molecular bridge structure, significantly improving the interfacial compatibility between PE and asphalt and enhancing the road performance of the modified asphalt.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing biomimetic grafted polyethylene (activated PE, biomimetic grafted PE, BG-PE), comprising the following steps: Oxidize polyethylene to obtain oxidized polyethylene (O-PE). The oxidized polyethylene and dopamine hydrochloride neutralization buffer solution were mixed to obtain polydopamine biomimetic polyethylene (PDA biomimetic PE, B-PE). The biomimetic grafted polyethylene is obtained by mixing the polydopamine biomimetic polyethylene, silane coupling agent and solvent.

[0006] Preferably, the mass ratio of the oxidized polyethylene to dopamine hydrochloride is 1:1.

[0007] Preferably, the mass ratio of the polydopamine biomimetic polyethylene to the silane coupling agent is 1:2.

[0008] Preferably, the silane coupling agent includes KH550.

[0009] The present invention also provides a biomimetic grafted polyethylene prepared by the preparation method described in the above technical solution.

[0010] This invention also provides the application of the biomimetic grafted polyethylene described in the above technical solution in the field of asphalt modification.

[0011] The present invention also provides a modified asphalt, which is prepared by sequentially shearing and developing the biomimetic grafted polyethylene and matrix asphalt described in the above technical solution.

[0012] Preferably, the amount of biomimetic grafted polyethylene is 3% to 6% of the mass of the base asphalt.

[0013] Preferably, the shearing parameters include: a shearing temperature of 175~185℃, a shearing time of 30~60min, and a shearing rate of 4000rad / min.

[0014] Preferably, the development temperature is 165°C and the time is 30 minutes.

[0015] This invention provides a method for preparing biomimetic grafted polyethylene, comprising the following steps: oxidizing polyethylene to obtain oxidized polyethylene; mixing the oxidized polyethylene with a dopamine hydrochloride neutralization buffer solution to obtain polydopamine biomimetic polyethylene; and mixing the polydopamine biomimetic polyethylene with a silane coupling agent and a solvent to carry out a grafting reaction to obtain the biomimetic grafted polyethylene.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention employs biomimetic synergistic grafting modification of polyethylene using polydopamine (PDA) and a silane coupling agent. After biomimetic grafting treatment with PDA and the silane coupling agent, the PE surface changes from smooth and flat to rough and fluffy, accompanied by a distinct granular adhesion structure. Simultaneously, NH and Si-O active functional groups are introduced onto the surface. Compared to ordinary PE, biomimetic grafted PE exhibits stronger surface polarity, a reduced difference in solubility parameters between it and asphalt, and an increased binding energy, significantly improving their compatibility. From a molecular mechanism perspective, dopamine first forms an initial PDA layer on the PE surface through oxidative self-polymerization. Subsequently, the silanol groups generated by the hydrolysis of the silane coupling agent undergo a dehydration condensation reaction with the PDA, while the active organic functional groups at the other end enhance the interfacial interaction between it and the asphalt components, thereby constructing a stable interfacial bonding structure. Furthermore, biomimetic grafted PE-modified asphalt exhibits superior high-temperature deformation resistance, fatigue resistance, and low-temperature crack resistance. Moreover, the preparation method of this invention is simple to operate and suitable for industrial application.

[0017] Data from the examples show that the synergistic modification of PDA and silane coupling agents can effectively improve the interfacial compatibility between waste PE and asphalt, providing a new technical path for the high-value utilization of waste plastics in road materials.

[0018] This invention also provides a biomimetic grafted polyethylene prepared by the preparation method described above. This invention utilizes a biomimetic grafting modification method of PDA and silane coupling agent to construct a "PE-PDA-silane coupling agent-Asphalt" dual-interface molecular bridge structure, which significantly improves the interfacial compatibility between PE and asphalt and enhances the road performance of modified asphalt.

[0019] This invention also provides a modified asphalt, wherein the amount of biomimetic grafted polyethylene is limited to 3% to 6% of the mass of the base asphalt. When the PE content is low, its effect on improving the performance of asphalt is limited, while when the content is too high, it is easy to cause segregation of the system and reduce the storage stability of the modified asphalt. Shear time, shear temperature, shear rate and development time are key process parameters affecting the performance of modified asphalt. If the shear temperature is too low, the shear time is insufficient or the shear rate is too low, it will lead to uneven dispersion of PE in the asphalt system and insufficient absorption and swelling, making it difficult to form a stable modified structure. If the shear time is too long or the shear temperature is too high, it may cause short-term aging of the asphalt, destroy the three-dimensional network structure inside the system, thereby weakening the modification effect. Attached Figure Description

[0020] Figure 1 For molecular models; Figure 2 Images (a) and (b) are SEM images of different locations on the waste PE material; Figure 3Images (a) and (b) are SEM images of different locations on the biomimetic grafted PE. Figure 4 FTIR images of PE before and after biomimetic grafting treatment; Figure 5 XPS spectra before and after biomimetic grafting treatment; Figure 6 The C1s spectrum of PE; Figure 7 The C1s spectrum of biomimetic grafted PE; Figure 8 The response surface plot shows the effect of the AB interaction on the ductility. Figure 9 A contour plot showing the effect of AB interaction on ductility; Figure 10 The response surface plot shows the effect of AC interaction on ductility. Figure 11 A contour plot showing the effect of AC interaction on ductility; Figure 12 The response surface plot shows the effect of the BC interaction on the ductility. Figure 13 A contour plot showing the effect of the BC interaction on the ductility; Figure 14 The results are for the complex shear modulus (G*) and phase angle (δ). Figure 15 The rutting factor for different asphalt samples at various test temperatures; Figure 16 The mean elastic recovery rate R 0.1 R 3.2 A bar chart; Figure 17 The non-recoverable creep compliance Jnr 0.1 and Jnr 3.2 A bar chart; Figure 18 Diagram illustrating the mechanism for enhanced creep recovery performance; Figure 19 A comparison chart of stiffness modulus; Figure 20 This is a comparison chart of creep rates; Figure 21 The thermal storage stability diagrams for each modified asphalt sample are shown. Figure 22 This is a fluorescence microscopy test image; Figure 23 This is a fluorescence distribution image; Figure 24 FTIR images of three asphalt samples; Figure 25 This is a comparison chart of solubility analysis results; Figure 26 Diagrams showing the binding energy between different asphalt mixture systems and biomimetic grafted PE with saturated components, aromatic components, resins, and asphaltenes; Figure 27 Microscopic mechanism diagram of PDA and KH550 biomimetic grafted PE to improve asphalt compatibility. Detailed Implementation

[0021] This invention provides a method for preparing biomimetic grafted polyethylene, comprising the following steps: Polyethylene is oxidized to obtain oxidized polyethylene; The oxidized polyethylene and the dopamine hydrochloride neutralization buffer solution were mixed to produce biomimetic polydopamine biomimetic polyethylene. The biomimetic grafted polyethylene is obtained by mixing the polydopamine biomimetic polyethylene, silane coupling agent and solvent.

[0022] Unless otherwise specified, all raw materials used in this invention are commercially available products in the field.

[0023] This invention oxidizes polyethylene to obtain oxidized polyethylene.

[0024] In this invention, the polyethylene is preferably waste polyethylene.

[0025] In this invention, the oxidant used for oxidation preferably includes a hydrogen peroxide solution, and the present invention does not have a particular limitation on the concentration of the hydrogen peroxide solution.

[0026] In this invention, the polyethylene is preferably placed in the hydrogen peroxide solution and stirred for 1 hour to carry out the oxidation.

[0027] After the oxidation is completed, the resulting oxidation product is preferably washed with deionized water and dried to obtain the O-PE.

[0028] Before the oxidation process, it is preferable to remove impurities from the surface of the PE. The surface removal process preferably includes the following steps: placing the PE in a Soxhlet extractor, adding acetone for extraction for 2 hours, washing the PE powder with deionized water after extraction, and then drying it at 100°C to constant weight.

[0029] After obtaining oxidized polyethylene, the present invention mixes the oxidized polyethylene with a dopamine hydrochloride neutralization buffer solution to obtain polydopamine biomimetic polyethylene.

[0030] In this invention, the mass ratio of oxidized polyethylene to dopamine hydrochloride is preferably 1:1.

[0031] In this invention, the preferred temperature for the biomimetic process is room temperature, and the preferred time is 12 hours.

[0032] In this invention, the buffer solution is preferably a Tris buffer solution with a concentration of 10 mM and a pH of 8.5.

[0033] In this invention, 100 mL of Tris buffer is dissolved in 100 mg of dopamine hydrochloride, and then 100 mg of O-PE is mixed with it. The mixture is magnetically stirred at room temperature for 12 h, at which point the white dispersion turns into a yellow solution. Finally, the resulting mixture is centrifuged at 12000 r / min for 20 min, and then washed three times with deionized water. The treated PE is dried at 80 °C to constant weight to obtain the polydopamine biomimetic polyethylene, which is a yellow powder.

[0034] After obtaining B-PE, the present invention mixes the polydopamine biomimetic polyethylene, silane coupling agent and solvent to carry out a grafting reaction to obtain the biomimetic grafted polyethylene.

[0035] In this invention, the preferred mass ratio of the polydopamine biomimetic polyethylene to the silane coupling agent is 1:2. If the amount of the silane coupling agent is too small, the interface modification effect cannot be fully utilized, and the adhesion strength improvement is limited. If the amount is too large, it is easy to cause compatibility problems in the asphalt system (if the mass fraction of the silane coupling agent is too large, it is easy to cause the powder to become sticky after treatment and to clump after drying, resulting in uneven distribution in the asphalt).

[0036] In this invention, the silane coupling agent preferably includes KH550.

[0037] In this invention, the preferred mass ratio of the silane coupling agent to the solvent is 2:100.

[0038] In this invention, the solvent preferably includes water and anhydrous ethanol, and the mass ratio of water to anhydrous ethanol is preferably 3:7.

[0039] In this invention, the grafting reaction is preferably carried out at room temperature for 2 hours.

[0040] In this invention, a solvent is prepared by placing water and anhydrous ethanol in a magnetic stirrer at a mass ratio of 3:7 at room temperature. Then, a silane coupling agent is added dropwise, and the mixture is stirred with a magnetic stirrer for 2 hours to hydrolyze the solution and obtain a silane coupling agent reaction solution. The B-PE is then added to the silane coupling agent reaction solution and stirred for 4 hours to carry out the grafting reaction.

[0041] After the grafting reaction is completed, the present invention preferably takes out the obtained solid and washes it repeatedly with deionized water three times, and then dries it at 80°C to constant weight to obtain the biomimetic grafted PE.

[0042] This invention also provides biomimetic grafted polyethylene prepared by the preparation method described above. This invention utilizes dopamine hydrochloride to form a PDA coating layer. The PDA coating layer has various active functional groups such as phenolic hydroxyl, amino, and imino groups, which can serve as active sites for interfacial reactions, providing a basis for subsequent functionalized grafting. By synergistically applying PDA and silane coupling agents to PE surface modification, a stable dual-interfacial bridging structure can be constructed, thereby significantly improving the interfacial compatibility between PE and asphalt and enhancing the road performance of the modified asphalt.

[0043] This invention also provides the application of the biomimetic grafted polyethylene described in the above technical solution in the field of asphalt modification.

[0044] The present invention also provides a modified asphalt, which is prepared by sequentially shearing and developing the biomimetic grafted polyethylene and matrix asphalt described in the above technical solution.

[0045] In this invention, the preferred dosage of the biomimetic grafted polyethylene is 3% to 6% of the mass of the base asphalt, specifically 3%, 4%, 5% or 6%. When the PE dosage is low, its effect on improving the performance of asphalt is limited, while when the dosage is too high, it is easy to cause segregation of the system and reduce the storage stability of the modified asphalt.

[0046] In this invention, the preferred parameters for shearing include: a shearing temperature of 175~185℃, specifically 175, 180, or 185℃; a shearing time of 30~60 min, specifically 30, 45, or 60 min; and a shearing rate of 4000 rad / min. Shearing time, shearing temperature, shearing rate, and development time are key process parameters affecting the performance of modified asphalt. If the shearing temperature is too low, the shearing time is insufficient, or the shearing rate is too low, it will lead to uneven dispersion of PE in the asphalt system and insufficient absorption and swelling, making it difficult to form a stable modified structure. If the shearing time is too long or the shearing temperature is too high, it may cause short-term aging of the asphalt, destroying the three-dimensional network structure inside the system, thereby weakening the modification effect.

[0047] In this invention, the development temperature is preferably 165°C and the development time is preferably 30 min.

[0048] This invention also provides a method for preparing the modified asphalt described in the above technical solution, comprising the following steps: Melt the base asphalt to obtain molten asphalt; The molten asphalt and biomimetic grafted polyethylene are pre-mixed, and then subjected to shearing and development in sequence to obtain the modified asphalt.

[0049] In this invention, the melting temperature is preferably 145°C, and the melting is preferably carried out in an oven.

[0050] In this invention, the biomimetic grafted polyethylene is preferably added to the molten asphalt in batches. This invention does not have any special limitations on the number of batches or the amount of each batch.

[0051] In this invention, the purpose of pre-stirring is to initially and uniformly disperse the raw materials. This invention does not impose any special limitations on the parameters of the pre-stirring.

[0052] In this invention, the pre-stirring is preferably done using a glass rod.

[0053] In this invention, the shearing is preferably performed in a high-speed shearing device.

[0054] In this invention, the development is preferably carried out in an oven.

[0055] This invention utilizes response surface methodology to optimize the design, clarifying the optimal preparation parameters for modified asphalt and the optimal dosage of biomimetic grafted PE, and establishes predictive models for these parameters. Then, the dispersion effect of biomimetic grafted PE in asphalt is analyzed using digital fluorescence microscopy. The high- and low-temperature rheological properties and fatigue properties of the biomimetic grafted PE modified asphalt are evaluated using DSR, MSCR, LAS, and BBR experimental systems. Finally, molecular dynamics simulations are employed to elucidate the interaction mechanism between the biomimetic grafted PE and the asphalt matrix based on binding energy, solubility parameters, and relative concentration distribution.

[0056] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0057] Example 1 I. Raw Material Selection: Base asphalt AH-70# road petroleum asphalt produced by Dongming Petrochemical Group was selected as the base asphalt, and the basic performance indicators of the asphalt were tested. The results are shown in Table 1. The experimental results all meet the requirements of the specifications.

[0058] Table 1 Basic Technical Indicators of 70# Base Asphalt

[0059] Waste PE The selected material is 100-mesh polyethylene produced by Hengfa Plastics Co., Ltd., which is a white powder. Its basic properties are shown in Table 2.

[0060] Table 2 Basic Properties of Waste PE

[0061] chemical All reagents used in this invention were of analytical grade and were used directly without further purification. The silane coupling agent KH550 (NH2(CH2)3Si(OC2H5)3) was provided by Kangjin New Materials Technology Co., Ltd., and its main technical specifications are shown in Table 3. Dopamine hydrochloride was purchased from Shanghai Aladdin Reagent Co., Ltd.; tris(hydroxymethyl)aminomethane hydrochloride (dissolved in Tris buffer) pH=8.5.

[0062] Table 3 Technical Specifications of KH550

[0063] II. Experimental Procedure: 1. Box-Behnken Experiment Design Preparation of biomimetic grafted PE Before performing biomimetic grafting activation treatment, the PE surface needs to be cleaned. The PE is placed in a Soxhlet extractor, and acetone is added for extraction for 2 hours. After extraction, the PE powder is washed with deionized water and then dried at 100°C to constant weight. Subsequently, the PE is placed in a hydrogen peroxide solution, stirred for 1 hour, washed again with deionized water, and dried to obtain oxidized PE. The biomimetic process of PE is as follows: 100 mL (10 mM, pH=8.5) of Tris buffer and 100 mg of dopamine hydrochloride were mixed and magnetically stirred until fully dissolved. O-PE was then added, and the mixture was magnetically stirred at room temperature for 12 h. As the reaction proceeded, the color of the system gradually changed from milky white to brownish-yellow. Finally, the mixture was centrifuged at 12000 r / min for 20 min, washed three times with deionized water, and the treated PE was dried at 80℃ to constant weight to obtain PDA biomimetic PE, which is a yellow powder. The PE grafting process is as follows: First, at room temperature, distilled water and anhydrous ethanol are mixed in a magnetic stirrer at a mass ratio of 3:7 to prepare an ethanol solution. Then, 2.0% KH550 (KH550:ethanol solution = 2:100) is added dropwise, and the mixture is stirred with a magnetic stirrer for 2 hours for hydrolysis. B-PE is then added to the prepared silane coupling agent reaction solution (B-PE to KH550 mass ratio is 1:2), and stirred for 4 hours. After stirring, the PE is removed and washed three times repeatedly with deionized water, then dried at 80°C to constant weight, resulting in biomimetic grafted PE, denoted as BG-PE.

[0064] Preparation of modified asphalt A measured amount of base asphalt was heated to complete melting in a 145℃ oven. Three mass fractions of BG-PE (3%, 4%, and 5%) were added to the molten base asphalt, and modified asphalt was prepared using a high-speed shearing method. Different amounts of BG-PE were added to the molten asphalt in batches and pre-stirred with a glass rod. After the system temperature reached the set shearing temperature, high-speed shearing equipment was used for shear blending under set conditions. After shearing, the resulting modified asphalt was placed in a 165℃ oven for 30 minutes for development. Upon completion of development, biomimetic grafted PE modified asphalts at different processing levels were obtained.

[0065] This invention is based on Box-Behnken optimization design in response surface methodology. It adopts a three-factor, three-level design method, taking the biomimetic grafted PE dosage, shear time, and shear temperature as independent variables, and the penetration, softening point, and ductility as response variables. The level and gradient settings of each factor are shown in Table 4.

[0066] Table 4 Experimental Design

[0067] 2. Testing and Characterization 2.1 Microscopic performance testing (1) Scanning electron microscopy (SEM) experiment The surface morphology of PE before and after biomimetic grafting was analyzed using a ZEISS Sigma 360 field emission scanning electron microscope manufactured in Germany. The applied voltage was 5kV, and the sample surface was treated with gold sputtering. The sample magnification was 2000x and 5000x.

[0068] (2) Fourier transform infrared spectroscopy (FTIR) Thermo Fisher IS5 infrared spectrometer was used to analyze the characteristic peak positions and functional group changes of PE before and after biomimetic grafting and modified asphalt. The scanning range was 4000~4000 cm⁻¹. -1 The scans were performed 32 times, and the FTIR data were processed and analyzed using OMNIC software.

[0069] (3) X-ray electron spectroscopy (XPS) The elemental composition of PE before and after biomimetic grafting was analyzed using a Thermo Scientific Escalab 250Xi X-ray electron spectrometer. The excitation source was Al Ka ​​rays (E=1486.68 eV), with a voltage of 14878.80 V and a current of 8.5 mA. The pass energy spectrum was 100 eV, the fine spectrum was 20 eV, the step size was 0.05 Ev, and the residence time was 40–50 ms.

[0070] (4) Fluorescence microscopy (FM) A small amount of asphalt binder solution was dropped onto a clean glass slide, and a coverslip was placed on top from the side to avoid air bubbles. The microstructure of the base asphalt and the 4% composite modified asphalt was then tested using an Opal fluorescence microscope manufactured in Shanghai, China, at a magnification of 200x.

[0071] 2.2 Traditional Physical Properties of Asphalt Based on the standard of test procedure for asphalt and asphalt mixtures in highway engineering (JTG 3410-2025), traditional physical property tests of penetration, softening point and ductility were conducted on base asphalt and modified asphalt.

[0072] 2.3 Rheological property testing (1) Temperature scanning experiment The high-temperature rheological properties of asphalt binders were determined using an MCR-301 dynamic shear rheometer manufactured in Germany. The temperature scan frequency was set to 10 rad / s, the rotating shaft diameter was 25 mm, the heating rate was 0.7 °C / s, and the distance between the rotating shaft and the base plate was 1 mm. Strain control (ε=12%) was used in the test. The temperature scan range was 40–82 °C, with intervals of 6 °C. The test results included complex shear modulus, phase angle, and the rutting factor was calculated.

[0073] (2) Linear Amplitude Scan Experiment (LAS) Linear amplitude scanning tests were used to characterize the mid-temperature fatigue properties of base asphalt and modified asphalt. The test temperature was 25℃, the loading frequency was 10Hz, and a sinusoidal loading pattern was adopted. The strain amplitude gradually increased from 0.1% to 30%, and 31 different strain levels were applied to the asphalt material. Each strain lasted for 10s, and the fatigue characteristic parameters of various asphalt binders were determined according to Equation 1.

[0074] Formula 1, Among them, C (t) C represents the asphalt integrity parameter; D represents the value of |G|sin δ at a specific strain level of 0.1%; f It is the asphalt damage variable; D (t) The variable represents the asphalt damage at time t; C1, C2, b, A, B, and k are fitting parameters related to fatigue life; a represents the rheological characteristic parameter; m is obtained from the swept frequency test through frequency calculation; G (w) Indicates energy storage modulus; w represents frequency, Hz; N f For the fatigue life of asphalt; γ max It represents the maximum expected strain level of the asphalt; f is the loading frequency, 10Hz.

[0075] (3) Multiple stress creep recovery test (MSCR) The MSCR test was used to characterize the high-temperature repeated creep characteristics of asphalt binders. The test temperature was 60℃, and the stress levels were 0.1 kPa and 3.2 kPa. Ten loading-unloading cycles were performed at each stress level, with each cycle lasting 10 s. Based on the strain-time data of various asphalt binders, the elastic recovery rate (R) and irreversible creep compliance (J) were calculated using the following formulas. nr As shown in Equation 2.

[0076] Equation 2, Where, ε p ε represents the maximum strain reached during each loading cycle. u This corresponds to the residual strain remaining after recovery; σ represents the stress level, with values ​​of 0.1 kPa and 3.2 kPa.

[0077] (4) Bending beam rheological test (BBR) The low-temperature rheological properties of asphalt binders were tested using a TE-type bending beam rheometer manufactured by Cannon Industries, Inc., USA. Temperatures selected were -12, -18, and -24°C. In a low-temperature constant-temperature bath, a constant load was applied to the middle section of an asphalt beam, and the test results included stiffness modulus S and creep rate m.

[0078] 3. Establishment and optimization of molecular dynamics models This invention employs the AAA-1 twelve-component asphalt model to construct a matrix asphalt system. Based on the four-component theory of asphalt, this model consists of 12 representative molecules: asphaltenes, resins, aromatics, and saturates. Its basic parameters are shown in Table 5. The model predicts a system density of 0.99 g / cm³ at 298.15 K. 3 The density is consistent with the measured density (1.00~1.02 g / cm³). 3 The results are relatively close, with an error of less than 3%. Furthermore, this model can effectively characterize the macroscopic properties of actual asphalt, such as density, solubility parameters, and rheological response. It exhibits high reliability in asphalt molecular dynamics simulations and is therefore widely used in the study of interfacial interactions and microscopic mechanisms in modified asphalt systems.

[0079] Considering that PDA is formed by the oxidative self-polymerization of dopamine under weakly alkaline conditions, its typical oxidative structural unit is used as the molecular model of PDA; at the same time, considering that KH550 generates silanol groups after hydrolysis, its hydrolysis product is used as the molecular model of silane coupling agent.

[0080] The molecular structures of each component were built using Materials Studio, and the geometry was optimized using the Forcite module to obtain stable molecular configurations, such as... Figure 1As shown in the figure. Based on this, a blend system of base bitumen, PE-modified bitumen, and biomimetic grafted PE-modified bitumen was constructed using the Amorphous Cell module, with an initial density set to 0.1 g / cm³. 3 The model was then optimized for energy using the Forcite module to eliminate unreasonable contacts in the initial structure, and annealing was performed under the NPT ensemble to improve system stability. After annealing, kinetic equilibrium simulations were conducted at 298 K and 1 atm for 500 ps, ​​with a time step of 1 fs. Simulation results showed that the system density remained stable between 0.98 and 1.01 g / cm³. 3 Within the specified range, the total energy fluctuation is small, indicating that the model has reached a stable equilibrium state. Finally, equilibrium structure models for base asphalt, PE-modified asphalt, and biomimetic grafted PE-modified asphalt are obtained, as follows: Figure 2 As shown.

[0081] Table 5. Twelve Components of Asphalt

[0082] III. Test Results 3.1 Characterization of grafted activated PE 3.1.1 SEM SEM scans were performed on PE before and after biomimetic grafting, and the surface microstructure was as follows: Figures 2-3 As shown. Figure 2 Images (a) and (b) are SEM images of different locations in the waste PE. Figure 3 Images (a) and (b) show SEM images of different locations on the biomimetic grafted PE. It can be seen that the untreated PE surface is relatively smooth and flat, with a dense structure and regular morphology, indicating low surface activity. This is not conducive to effective interaction between the PE and asphalt components, resulting in poor compatibility. After biomimetic grafting, the PE surface morphology changes significantly, with numerous granular protrusions appearing on the surface, and the interface exhibiting obvious roughening. This indicates that PDA and KH550 have been successfully deposited and adhered to the PE surface. Compared to the original smooth and inert PE surface, the surface roughness of the biomimetic grafted PE is significantly increased, and the surface activity is enhanced. This is beneficial for strengthening the interfacial adsorption between the PE and asphalt, promoting the bonding between the two phases, thereby improving interfacial compatibility and enhancing the stability of the modified system.

[0083] 3.1.2 FTIR FTIR was used to test the changes in functional groups on the PE surface before and after biomimetic grafting treatment to reveal the microscopic mechanism of its surface modification. The test results are as follows: Figure 4 As shown, the original PE values ​​are 2926.6 and 2848.6 cm². -1 A strong absorption peak appears at 1463.3 cm⁻¹, corresponding to the antisymmetric and symmetric stretching vibrations of -CH₂, respectively.-1 The absorption peaks at 1357.57 and 1308 cm⁻¹ correspond to the in-plane bending vibration of -CH₂. -1 The absorption peak at 717.8 cm⁻¹ corresponds to the CO stretching vibration; -1 The rocking vibration at -CH2 is a typical characteristic absorption peak for polyethylene. Additionally, at 1626.1 cm⁻¹... -1 A weak absorption peak was observed nearby, corresponding to the stretching vibration of the C=C bond. Compared to the original PE, the FTIR spectrum of the biomimetic grafted PE showed significant changes. At 3449.5 cm⁻¹... -1 A distinct, broad absorption band appeared at this location, primarily originating from the overlapping stretching vibrations of -NH and -OH groups, indicating successful PDA deposition on the PE surface. Meanwhile, at 1626.1 cm⁻¹... -1 The nearby absorption peaks are significantly enhanced, corresponding to the C=C bond stretching vibration and NH bending vibration in the aromatic structure, further verifying the formation of the PDA layer.

[0084] In addition, at 1133.56cm -1 and 1046.02cm -1 The appearance of new characteristic absorption peaks nearby corresponds to the stretching vibrations of Si-OC and Si-O-Si bonds, respectively, indicating that the silanol groups formed after KH550 hydrolysis undergo a dehydration condensation reaction with the PDA layer to form a stable silicon-oxygen network structure. Simultaneously, peaks at 1463.3 and 717.8 cm⁻¹ are observed. -1 The presence of PE characteristic peaks indicates that the biomimetic grafting process mainly occurs on the surface of the PE molecular chain and does not cause significant damage to its main structure.

[0085] In summary, the FTIR results show that PDA and KH550 have been successfully synergistically grafted onto the PE surface. While preserving the integrity of the PE main structure, active functional groups such as amino, hydroxyl and siloxane bonds are introduced, thereby improving the surface activity of PE and providing favorable conditions for enhancing the interfacial interaction between PE and asphalt components.

[0086] 3.1.3 XPS To further analyze the changes in elemental composition and chemical bond structure of the PE surface after biomimetic grafting treatment, XPS experiments were used for characterization. The test results are shown below. Figures 5-7 See Table 6. Figure 5 XPS spectra before and after biomimetic grafting treatment. Figure 6 The C1s spectrum of PE, Figure 7The image shows the C1s spectrum of biomimetic grafted PE. It can be seen that after biomimetic grafting treatment, the C content on the PE surface decreased from 86.70 wt% to 80.84 wt%, while the O content increased from 12.75 wt% to 15.72 wt%. This is mainly due to the oxidation reaction that occurred during the biomimetic grafting process, where some methyl and methylene groups were oxidized to generate oxygen-containing functional groups, leading to an increase in surface oxygen content. Simultaneously, N and Si elements were detected on the treated PE surface, while no corresponding signals were observed in the original PE, indicating that nitrogen-containing PDA and silicon-containing KH550 were successfully grafted onto the PE surface, further verifying the effectiveness of the biomimetic grafting modification. The PE surface before and after biomimetic grafting treatment was dominated by CH / CC bonds, with relative contents of 83.3% and 78.5%, respectively. Compared with the original PE, the relative content of CH / CC bonds in the biomimetic grafted PE decreased by 4.8%, indicating that some CH bonds participated in the oxidation reaction during the grafting process. Meanwhile, the relative content of COC bonds increased from 11.2% to 14.9%, indicating that more oxygen-containing functional groups were introduced onto the PE surface. This is consistent with the FTIR analysis results and further confirms the occurrence of oxidation reaction and the successful introduction of active functional groups during the biomimetic grafting process.

[0087] Table 6 XPS Element Content

[0088] 3.2 Experimental Results and Analysis of Response Surface Method 3.2.1 Response Value Analysis Modified asphalt was prepared under different process parameters, and its penetration at 25℃, softening point, and ductility at 5℃ were tested. The test results are shown in Table 7. Regression analysis was performed on each response value using Design-Expert software to establish a response surface prediction model, and the significance of the model was verified. The analysis results are shown in Table 8. It can be seen that all three response indicators showed obvious changing patterns, and the established models all reached a significant level (p < 0.05). The lack-of-fit terms were not significant (p > 0.05), indicating that the model has good fitting accuracy and predictive ability, and can accurately reflect the influence of various factors on the performance of modified asphalt.

[0089] Table 7 Box-Behnken Test and Results

[0090] Table 8 Results of significance analysis of response values

[0091] 3.2.2 Establishment and Reliability Analysis of Regression Equation Model Using ductility as the response index, a quadratic nonlinear regression was performed using Design-Expert software to establish a response surface regression equation, providing a basis for Box-Behnken experimental design analysis. The resulting regression model is shown in Equation 3.

[0092] Ductility=24.84-3.34A-0.2125B-0.1C-0.3AB-0.325AC-0.225BC-1.87A 2 -1.17B 2 -1.29C 2 Formula 3.

[0093] The results of the ANOVA for the ductility regression model are shown in Table 9. The model F-value is 154.57, P < 0.0001, indicating that the model is significant overall. The F-value for the lack-of-fit term is 2.9, P = 0.1652 > 0.10, indicating that the model lack of fit is not significant and the fitting bias is small. Comprehensive analysis shows that, at the 95% confidence level, this quadratic regression equation model can well describe the influence of various factors on ductility, and the independent variables in the model have a significant impact on ductility. (Coefficient of determination R0) 2 The closer the value is to 1, the better the model fit. In this invention, the coefficient of determination R of the ductility model... 2 The adjusted coefficient of determination is 0.9950. 2 The value is 0.9427, and the difference between the two is less than 0.2, indicating that the model has good fitting accuracy and reliability, and can effectively reflect the response law of the ductility of biomimetic grafted PE modified asphalt with changes in various factors.

[0094] The Box-Behnken experiments revealed that BG-PE content, shear time, and shear temperature all significantly affected ductility. Specifically, an appropriate amount of BG-PE absorbs lightweight components and swells in the asphalt system, forming a network structure that enhances the bonding between asphalt molecules and improves ductility. However, excessively high BG-PE content significantly increases system viscosity, restricts molecular chain movement, and leads to a decrease in ductility. Furthermore, shear time and shear temperature directly affect the dispersion and swelling degree of BG-PE in asphalt. Suitable process conditions promote the formation of a homogeneous and stable modified system, while excessively high temperatures or prolonged shear times may cause asphalt aging or disrupt the system's stable structure, thereby reducing ductility.

[0095] The same method was used to perform regression analysis on penetration and softening point, and the response surface regression equations for penetration (Pen) and softening point (Spt) were obtained, as shown in Equations 4 and 5.

[0096] Needle penetration = 60.9 - 4.88A - 0.2625B - 1.04C + 0.25AB + 0.4AC + 0.025BC - 3.44A 2-2.01B 2 -2.81C 2 Equation 4; Softening point = 70.32 + 4.94A + 0.3625B + 0.45C + 0.1AB + 0.275AC - 0.025BC - 2.61A 2 -3.81B 2 -1.54C 2 Formula 5.

[0097] Based on the above regression model, with the goal of achieving the optimal combination of penetration, softening point and ductility, the optimal preparation process parameters for biomimetic grafted PE modified asphalt were obtained by response surface optimization analysis: BG-PE content of 4%, shearing time of 45 min, and shearing temperature of 180℃.

[0098] Table 9. Variation of Length and Significance Test

[0099] 3.2.3 Response Surface Analysis Figure 8 The response surface plot shows the effect of the AB interaction on the ductility. Figure 9 This is a contour plot showing the effect of the AB interaction on the ductility. Figure 10 This is a response surface plot showing the effect of the AC interaction on the ductility. Figure 11 This is a contour plot showing the effect of AC interaction on ductility. Figure 12 The response surface plot shows the effect of the BC interaction on the ductility. Figure 13The contour plots show the effect of the BG-PE interaction on ductility. The slope of the response surface and the shape of the contour lines reflect the significance of the interaction between factors. A steeper surface and a more elliptical contour line indicate a more significant interaction. It is evident that the surface changes of the response plots for the interaction between the biomimetic grafted PE content and shear time, and between the biomimetic grafted PE content and shear temperature, are quite significant, indicating that the interaction of both sets of factors has a significant impact on the ductility of the modified asphalt. When the BG-PE content is between 3% and 4%, the shear time is between 35 and 55 minutes, and the shear temperature is between 175 and 185°C, the contour lines are relatively regular elliptical, and the ductility is higher in the corresponding region. This is mainly because an appropriate amount of BG-PE can be uniformly dispersed in the asphalt system and, through absorption of lightweight components, swells to form a network structure, thereby enhancing the system's ductility. However, excessive BG-PE is prone to local agglomeration, weakening its dispersion effect and leading to a decrease in ductility. The response surface plot of the interaction between shear time and shear temperature shows significant changes, and the contour plot is elliptical, indicating that the interaction between the two is equally significant. Appropriate shear time and temperature are beneficial to the full dispersion and swelling of PE in asphalt, promoting the formation of a stable modified structure; while excessively high temperature or shear time may cause asphalt aging and destroy the already formed stable structure, thereby reducing ductility properties.

[0100] 3.3 Rheological Properties of Composite Modified Asphalt (Base Asphalt (MA), PE Modified Asphalt (PEMA), BG-PE Modified Asphalt (BGPEMA)) Unless otherwise specified, BG-PE modification used below refers to modified asphalt prepared with optimal process parameters. 3.3.1 Rheology To evaluate the modification effect of biomimetic grafted PE on the rheological properties of asphalt, dynamic shear rheology (DSR) temperature scanning tests were conducted on base asphalt, PE-modified asphalt, and biomimetic grafted PE-modified asphalt. The test results for complex shear modulus (G*) and phase angle (δ) are shown in [Figure number missing]. Figure 14As shown, temperature has a significant impact on the shear modulus and phase angle of asphalt binders. With increasing temperature, the G* value of each asphalt sample decreases, while the δ value gradually increases. This is mainly because increased temperature enhances the thermal motion of molecules within the system, weakens the constraint effect of the asphalt's internal structure, reduces the material's elastic response, and enhances its viscous flow characteristics, leading to a gradual shift of the asphalt towards a viscous flow dynamic, thus reducing its high-temperature deformation resistance. At the same temperature, the base asphalt has the lowest G* value and the highest δ value, indicating its weak elastic recovery and poor high-temperature stability. After incorporating PE, the modifier absorbs oil and swells in the asphalt matrix, forming a fine network structure, increasing the system's viscosity and structural stiffness, thereby increasing the G* and decreasing the δ of the modified asphalt, significantly improving its high-temperature stability. Compared to ordinary PE-modified asphalt, biomimetic grafted PE-modified asphalt exhibits a higher G* value and a lower δ value, indicating that biomimetic grafting treatment further enhances the elastic response of the modified system and improves its high-temperature stability. This is mainly attributed to the fact that the biomimetic grafting treatment significantly improves the surface polarity and interfacial activity of PE particles, enabling PDA and KH550 to construct a stable functionalized interfacial layer on the PE surface, enhancing the interfacial adhesion between PE and asphalt, improving the dispersion uniformity and interfacial bonding strength of the modifier in asphalt, thereby promoting the formation of a more stable continuous elastic phase of the modifier in the asphalt matrix, and improving the overall structural stability and elastic response of the system.

[0101] The rutting factor (G* / sin(δ)) is an important indicator for measuring the resistance of asphalt to permanent deformation at high temperatures. A higher G* / sin(δ) value indicates a stronger resistance to high-temperature rutting deformation. Based on the G* and δ test results, the rutting factors of different asphalt samples at various test temperatures are as follows: Figure 15 As shown, the base asphalt has the lowest G* / sin(δ) value, indicating its weakest high-temperature deformation resistance. This index significantly improves after modification with ordinary PE, mainly due to the swelling of PE particles through adsorption of lightweight components, forming a dispersed polymer-rich phase in the asphalt matrix, thereby enhancing the system's shear deformation resistance. The G* / sin(δ) value of biomimetic grafted PE modified asphalt is significantly higher than that of ordinary PE modified asphalt, indicating a further improvement in its high-temperature rutting resistance. This is because the biomimetic grafting treatment promotes the synergistic effect of PDA and KH550 on the PE surface, constructing a more stable interfacial bridging structure, enhancing the interaction force between PE and asphalt molecules, and improving the internal structural stability and overall shear deformation resistance of the system.

[0102] 3.3.2 Creep To further evaluate the high-temperature creep recovery characteristics of different modified asphalts, the average elastic recovery rate R under stress levels of 0.1 kPa and 3.2 kPa was calculated based on the MSCR test results. 0.1 R 3.2 and irreversible creep compliance Jnr0.1 and Jnr 3.2 The results are as follows: Figures 16-17 As shown. Figure 16 The mean elastic recovery rate R 0.1 R 3.2 The bar chart, Figure 17 The non-recoverable creep compliance Jnr 0.1 and Jnr 3.2 The bar chart shows that as the stress level increases from 0.1 kPa to 3.2 kPa, the cumulative strain of each asphalt sample increases significantly, and the proportion of unrecoverable deformation gradually increases, indicating that higher stress levels weaken the elastic recovery ability of the material and make the system more prone to permanent deformation.

[0103] Under the same stress level, the strain-time curve of base asphalt exhibits a clear stepwise growth characteristic, and its recovery deformation after unloading is relatively small, indicating that its creep deformation is mainly characterized by irreversible viscous flow deformation, and its resistance to permanent deformation at high temperatures is weak. In contrast, PE-modified asphalt exhibits a similar creep-recovery evolution law, but its cumulative strain is significantly lower than that of base asphalt, and its elastic recovery during the unloading recovery stage is more obvious, with the strain-time curve showing a certain recovery lag characteristic. This indicates that the incorporation of PE effectively enhances the elastic recovery ability of the asphalt system, while improving its resistance to shear deformation under high-temperature loads. This is mainly attributed to the absorption of lightweight components by PE particles in the asphalt and their swelling, gradually forming a dispersed spatial network structure, thereby enhancing the internal structural constraint of the system. Furthermore, the cumulative strain of biomimetic grafted PE-modified asphalt is significantly lower than that of ordinary PE-modified asphalt, and its recovery ability after unloading is further enhanced, indicating that it has superior resistance to permanent deformation. This is mainly attributed to the enhanced interfacial interaction between PE and asphalt after biomimetic grafting treatment. It can more fully absorb the lightweight components in the asphalt and form a more stable and continuous three-dimensional network structure in the asphalt matrix, thereby forming a more stable interfacial coupling structure and improving the stress transfer efficiency and elastic recovery ability of the system.

[0104] Mechanism of enhanced creep recovery performance, such as Figure 18 As shown in the figure, analysis reveals that a stable interfacial coupling structure is formed between the biomimetic grafted PE and asphalt. This structure can effectively store and release elastic energy under cyclic loading, thereby achieving more efficient elastic recovery and suppressing the accumulation of irreversible creep. Therefore, biomimetic grafted PE modified asphalt exhibits superior high-temperature resistance to permanent deformation and structural stability.

[0105] 3.3.3 Fatigue Analysis of the stress-strain curves at 25℃ revealed similar trends in all three asphalt samples when the strain was below 13%. Stress increased continuously with increasing strain, exhibiting a linear growth phase dominated by elasticity. This indicates that the internal structure of the material had not yet undergone significant damage, and recovery elastic deformation was the primary characteristic at this stage. As strain further increased, the base asphalt reached its peak stress, after which the stress rapidly decreased with increasing strain, indicating significant damage to the internal structure and a gradual decline in load-bearing capacity, exhibiting typical brittle instability characteristics. In contrast, the PE-modified asphalt maintained a certain stress plateau after reaching its peak stress, followed by a slow decrease in stress. This suggests that the incorporation of PE enhanced the deformation coordination of the asphalt system to some extent, delayed the expansion of internal structural damage, and resulted in the material exhibiting certain plastic energy dissipation characteristics. The biomimetic grafted PE-modified asphalt remained relatively stable after reaching its peak stress, without significant stress attenuation, demonstrating superior ductile deformation capacity and structural stability. This is mainly attributed to the biomimetic grafting treatment significantly improving the interfacial compatibility between PE and asphalt, enabling the formation of a more stable elastic response structure within the asphalt matrix. This structure can coordinate local stress distribution under external loads and enhance the system's ability to dissipate strain energy, thereby delaying structural failure caused by local stress concentration. Furthermore, the interfacial bridging structure synergistically constructed by PDA and KH550 enhances the interfacial adhesion between PE particles and asphalt molecules, improving the system's toughness and elastic recovery, enabling the material to maintain high load-bearing capacity even under large deformation conditions. Therefore, biomimetic grafted PE modified asphalt exhibits more stable stress retention and superior crack resistance, demonstrating significant advantages in improving the low-temperature toughness and damage resistance of asphalt.

[0106] 3.3.4 Low temperature Stiffness modulus (S) and creep rate (m) are important indicators for evaluating the low-temperature performance of asphalt. The smaller the S value, the better the low-temperature flexibility of the asphalt material; the larger the m value, the better the low-temperature stress relaxation ability of the asphalt material, which is more conducive to alleviating thermal shrinkage stress concentration and thus reducing the risk of low-temperature cracking. Figure 19 This is a comparison chart of stiffness modulus. Figure 20The creep rate comparison chart shows that the stiffness modulus of all asphalt samples increases with decreasing temperature. This is mainly because the molecular chain mobility of asphalt weakens at low temperatures, the viscoelastic transition of the system gradually approaches the glassy state, and some waxy components undergo ordered arrangement, further enhancing the rigid constraint effect of the system, thus leading to higher stiffness and brittleness characteristics. Compared with the base asphalt, the stiffness modulus of PE-modified asphalt and biomimetic grafted PE-modified asphalt are significantly reduced, indicating that the modification treatment can effectively improve the low-temperature flexibility of asphalt. Among them, the biomimetic grafted PE-modified asphalt has the lowest S-value, indicating that its low-temperature crack resistance is the best. This is mainly attributed to the biomimetic grafting treatment significantly enhancing the interfacial compatibility between PE and asphalt. The continuous elastic phase formed by the two can effectively disperse low-temperature shrinkage stress and alleviate local stress concentration, thereby reducing the overall stiffness of the system and improving the low-temperature flexibility of the material. As the temperature decreases, the creep rate of all asphalt samples gradually decreases. This is because asphalt is a typical temperature-sensitive viscoelastic material. When the temperature decreases, the free volume within the system decreases, and the mobility of molecular chains is suppressed, leading to a slower stress relaxation process and thus exhibiting a lower creep rate. According to the Superpave specification, when m < 0.3, it indicates that the asphalt sample has insufficient low-temperature crack resistance and is prone to low-temperature brittle fracture. The results show that the biomimetic grafted PE modified asphalt has the largest m value, indicating its strongest low-temperature stress relaxation ability. This is mainly because the elastic response structure formed between the biomimetic grafted PE and asphalt can achieve stress redistribution through elastic deformation under low-temperature conditions, thereby effectively improving the system's stress relaxation ability and enhancing its low-temperature crack resistance.

[0107] 3.4 Storage stability analysis (digital fluorescence analysis-grayscale analysis) 3.4.1 Analysis of Softening Point Difference Test To further evaluate the effect of biomimetic grafted PE on improving the storage stability of modified asphalt, thermal storage stability tests were conducted on various modified asphalt samples. Figure 21 It is evident that ordinary PE-modified asphalt exhibits significant segregation after high-temperature storage, with a large difference in softening points between its upper and lower layers, indicating poor compatibility between PE and the asphalt matrix and a strong tendency for phase separation. In contrast, the difference in softening points between the upper and lower layers of biomimetic grafted PE-modified asphalt is significantly reduced, indicating a marked improvement in its thermal storage stability. This improvement is mainly attributed to the enhanced interfacial compatibility between PE and asphalt through biomimetic grafting treatment. Specifically, the polar functional groups in the PDA layer enhance the interfacial interaction between PE and the polar components of asphalt, while the siloxane bridging structure formed by the hydrolysis and condensation of KH550 further improves the interfacial bonding strength. The synergistic effect of these two factors effectively reduces the tendency of PE particles to agglomerate in the asphalt matrix, enhances their dispersion stability in asphalt, thereby suppressing phase separation behavior under high-temperature storage conditions and improving the storage stability of the modified asphalt.

[0108] 3.4.2 Analysis based on digital FM images To observe the dispersion state of biomimetic grafted PE particles in asphalt binder, fluorescence microscopy (FM) testing was performed on biomimetic grafted PE modified asphalt at the optimal dosage. The results are as follows: Figure 22 As shown in the figure, the green fluorescent area represents the modifier phase BG-PE, and the black area represents asphalt. It can be seen that in the composite system formed by the modifier phase BG-PE and asphalt, the biomimetic grafted PE is mainly distributed in a dotted or flocculent manner, and the modifier phase exhibits a continuous distribution characteristic in the asphalt matrix, forming a polymer-rich continuous phase. This continuous polymer-rich phase helps to enhance the interfacial interaction between the modifier and asphalt and improve the overall stability of the system.

[0109] To quantitatively evaluate the uniformity of biomimetic grafted PE distribution in modified asphalt, ImageJ software was used to calculate the proportion of fluorescent area in each region, thus characterizing the dispersion of the modifier phase in the asphalt matrix. Figure 23 The fluorescence distribution image reflects the spatial distribution characteristics of the fluorescence area ratio in each segmented region through different color levels. The results show that the biomimetic grafted PE particles can be dispersed relatively uniformly in asphalt with less local agglomeration, indicating that the biomimetic grafting treatment significantly improves the compatibility between PE and asphalt, thereby enhancing its dispersion stability in the asphalt matrix.

[0110] 3.5 Mechanism analysis of grafted activated PE modification (FTIR) FTIR tests were performed on three asphalt samples, and the results are as follows: Figure 24 As shown in the figure. It can be seen that the base asphalt at 1300~1700cm and 2800~3000cm... -1 There are obvious absorption peaks within the range. Specifically, the peaks at 2851.7 and 2920.1 cm⁻¹ are... -1 The characteristic peaks at this location are mainly attributed to the asymmetric and symmetric stretching vibrations of -CH2 and -CH3 in the saturated hydrocarbon chains, indicating that the base asphalt contains abundant cycloalkanes and aliphatic hydrocarbon components, with the peak at 2920.1 cm⁻¹ being the most prominent. -1 The peak value is strongest at 1598.3 cm⁻¹, reflecting a high proportion of methylene structures in the system. -1 The nearby absorption peaks are mainly attributed to the stretching vibrations of conjugated C=C bonds in the aromatic ring skeleton, indicating that the matrix pitch contains a certain amount of aromatic compounds; 1451.2 cm⁻¹ -1 The nearby absorption peaks mainly originate from the bending vibrations of the -CH3 and -CH2 groups, while the peak at 1372.3 cm⁻¹... -1 The absorption peak corresponds to the symmetrical deformation vibration of -CH3. Compared with ordinary PE modified asphalt, biomimetic grafted PE modified asphalt exhibits a peak at 1028.15 cm⁻¹. -1 A new absorption peak appears at 1100 cm⁻¹, corresponding to the stretching vibration of the CN bond, and also at 1100 cm⁻¹.-1 A distinct Si-OC characteristic absorption peak was observed nearby, indicating that KH550 has been successfully grafted onto the PDA modified layer surface, forming a stable interfacial chemical bond. Furthermore, the biomimetic grafted PE-modified asphalt showed a peak at 720 cm⁻¹. -1 The intensity of the characteristic absorption peak corresponding to the PE crystal structure is significantly reduced, indicating that the grafting reaction reduces the original crystallinity of PE to a certain extent, thereby improving its dispersion ability and interfacial compatibility in the asphalt matrix.

[0111] From the perspective of interfacial reaction mechanism, PDA first forms a highly adhesive active intermediate layer on the PE surface through oxidative self-polymerization. This intermediate layer is rich in polar functional groups such as phenolic hydroxyl (-OH) and amino (-NH2), which can provide active sites for subsequent silane coupling agent reactions. Subsequently, KH550 undergoes hydrolysis to form silanol groups (Si-OH), which undergo a condensation reaction with the PDA layer to form stable Si-OC bonds. At the same time, the organic functional groups at the other end of the KH550 molecule can form stable bonds with polar components in asphalt through hydrogen bonding or physical adsorption, thereby constructing a molecular-scale interfacial bridging structure.

[0112] Therefore, a dual-interface bridging structure of "PE-PDA-KH550-Asphalt" is formed in the biomimetic grafted PE modified asphalt system. This structure not only significantly enhances the interfacial adhesion between PE and asphalt, effectively inhibiting the migration and aggregation of PE particles, but also promotes the uniform dispersion of the modifier phase in the asphalt matrix and forms a stable interfacial coupling structure. This structure can effectively adsorb and bind some lightweight components, promote the swelling of PE particles, and increase the proportion of elastic components in the system, thereby enhancing the high-temperature rutting resistance of the modified asphalt. At the same time, the continuous elastic network can effectively dissipate low-temperature shrinkage stress, delay crack initiation and propagation, thereby improving the low-temperature crack resistance of the modified asphalt.

[0113] 3.6 Compatibility simulation results of grafted activated PE and asphalt based on MS 3.6.1 Solubility Parameters Solubility parameters are important indicators for evaluating the thermodynamic compatibility of polymer-asphalt systems, and their magnitude is closely related to the cohesive energy density (CED) and molecular volume of the system. Based on the CED data of different asphalt systems (see Table 10), Equation 6 was used to calculate the solubility parameters of each system and their differences. Figure 25 This is a comparison chart of solubility analysis results.

[0114] δ=Ecoh / V Equation 6; In the formula, δ is the solubility parameter; Ecoh is the cohesive energy of the molecule; and V is the volume occupied by the molecule.

[0115] The smaller the difference in solubility parameters between two materials, the stronger the intermolecular interaction, and the easier it is for the system to form a stable and homogeneous blend structure. Calculation results show that the difference in solubility parameters between biomimetic grafted PE and asphalt is significantly smaller than that between unmodified PE and asphalt, indicating that biomimetic grafting significantly improves the thermodynamic compatibility between the two phases. Furthermore, the cohesive energy density (CED) of the biomimetic grafted PE-modified asphalt system is significantly higher than that of the ordinary PE-modified asphalt system, indicating enhanced intermolecular interactions and more stable interfacial bonding. This is mainly attributed to the stable interfacial bridging structure constructed by PDA and KH550 between PE and asphalt. PDA provides abundant polar activation sites, while KH550 forms a stable interfacial coupling layer through silicon-oxygen bonds, thereby enhancing the interaction between the polar components of PE and asphalt, increasing the interfacial bonding strength, and further improving the structural and storage stability of the blend system.

[0116] Table 10 CED of different asphalts

[0117] 3.6.2 Binding Energy To further reveal the interfacial interaction mechanism between biomimetic grafted PE and asphalt, the binding energy of different systems was analyzed. Binding energy characterizes the strength of the interaction between two phases; the larger the absolute value, the stronger the interfacial interaction, the more stable the blend system, and the better its compatibility. The formula for calculating binding energy is shown in Equation 7.

[0118] Ebinding = Eab - Ea - Eb (Equation 7); In the formula, Ebinding is the interfacial energy; Eab is the total energy of the blend system when it reaches a stable state; Ea is the energy of molecule a when it reaches a stable state; and Eb is the energy of molecule b when it reaches a stable state.

[0119] Generally, a positive Ebinding value indicates mutual repulsion between molecules within the mixture, which is detrimental to the formation of a stable structure; conversely, a negative value indicates mutual attraction between molecules, and the larger the absolute value, the more stable the interfacial bonding and the better the compatibility. The binding energy of different asphalt mixtures can be calculated using the formula, such as... Figure 26As shown, the binding energies of both modified systems are negative, indicating a significant attraction between the asphalt and the modifier. Compared to the ordinary PE modified system, the absolute value of the binding energy between the biomimetic grafted PE and asphalt is significantly increased, indicating that the grafting treatment significantly enhances the interfacial interaction strength between the two phases. Specifically, both van der Waals interaction energy and electrostatic interaction energy are increased, indicating that the interfacial bridging structure synergistically constructed by PDA and KH550 effectively enhances the intermolecular interaction between PE and asphalt. Furthermore, the difference in solubility parameters of the biomimetic grafted PE system is significantly reduced, further demonstrating that the biomimetic grafting treatment significantly improves the thermodynamic compatibility between PE and asphalt. This is mainly attributed to the polar functional groups introduced by the PDA layer increasing the surface polarity of PE, while the silicon-oxygen bridging network formed by KH550 enhances the interfacial constraint capacity, thereby reducing the difference in interfacial free energy and improving interfacial stability.

[0120] Furthermore, to further explore the interaction between biomimetic grafted PE and the four components of asphalt, the binding energy between biomimetic grafted PE and the saturated components, aromatic components, resins, and asphaltenes was calculated. The results are shown in [Figure number missing]. Figure 26 As shown, the binding energy between biomimetic grafted PE and the various components of asphalt follows the order: saturated components < asphaltene < aromatic components < resins (in terms of absolute binding energy). This result indicates that biomimetic grafted PE exhibits the strongest interfacial interaction with resins, followed by aromatic components and asphaltene, while the interaction with saturated components is relatively weak. This is mainly because grafting PDA and KH550 introduces a large number of polar functional groups onto the PE surface, enabling it to form stronger electrostatic interactions, hydrogen bonding, and van der Waals interactions with the polar groups and π-electron systems in resins and aromatic components, thus significantly enhancing the interfacial binding capacity. Simultaneously, biomimetic grafted PE also exhibits a strong interaction with asphaltene, further demonstrating that the interfacial bridging structure can effectively promote the adsorption and stable distribution of polar components on the PE surface. In contrast, since saturated components are mainly composed of nonpolar chain hydrocarbons, their interaction with biomimetic grafted PE mainly relies on weak dispersion interactions, resulting in a relatively low binding energy.

[0121] 3.6.3 Interaction between grafted activated PE and asphalt To reveal the microscopic mechanism by which PDA and KH550 biomimetic grafted PE improve asphalt compatibility at the molecular scale, the interfacial interaction process was analyzed, such as... Figure 27 As shown.

[0122] Due to the stable molecular chain structure of PE and the lack of active functional groups on its surface, direct chemical functionalization modification is difficult. Therefore, under ambient temperature and pressure, a polydopamine (PDA) coating layer is first deposited on the PE surface through the oxidative self-polymerization reaction of dopamine. This PDA layer has excellent interfacial adhesion and is rich in active functional groups such as phenolic hydroxyl, amino, and imine groups, which can serve as an active reaction platform for subsequent silane coupling agent reactions, providing reaction sites for further functionalization of the PE surface. Subsequently, KH550 generates highly reactive silanol groups (Si-OH) under hydrolysis conditions, which can undergo dehydration condensation with the phenolic hydroxyl groups in the PDA layer to form stable Si-OC covalent bonds, thereby achieving chemical grafting of KH550 onto the PE surface. The other end of the grafted KH550 molecule contains active organic functional groups, which can further interact with polar components in asphalt through hydrogen bonding, electrostatic adsorption, or physical entanglement, thus constructing a stable interfacial bridging structure between PE and asphalt. This structure significantly enhances the surface polarity of PE, strengthening its interfacial interaction with the polar components of asphalt. Furthermore, by forming a stable interfacial constraint layer, it effectively inhibits the migration and aggregation of PE particles in asphalt, promoting their uniform dispersion within the asphalt matrix. Ultimately, biomimetic grafted PE can form a stable and continuous three-dimensional network structure in asphalt, improving the interfacial compatibility between PE and asphalt at the molecular scale and providing theoretical support for improving the storage stability and road performance of modified asphalt.

[0123] In summary: This invention employs a synergistic grafting method of PDA and KH550 to surface activate PE, and systematically studies its impact on asphalt properties and its microscopic mechanism, yielding the following conclusions: 1. PDA and KH550 were successfully grafted onto the PE surface to construct a functionalized interface layer containing -OH, -NH2 and Si-OC bond structures, which significantly improved the polarity and interfacial reactivity of the PE surface, providing active sites for the subsequent effective binding with polar components of asphalt.

[0124] 2. Biomimetic grafted PE can form a stable and continuous three-dimensional network structure in asphalt, promote the uniform dispersion of modifiers and increase the content of elastic components in the system, thereby significantly enhancing the high-temperature deformation resistance of modified asphalt and improving its low-temperature crack resistance.

[0125] 3. Compared with ordinary PE modified asphalt, biomimetic grafted PE modified asphalt has a 15% higher softening point, a 30% higher rutting factor, and significantly improved thermal storage stability, indicating that biomimetic grafting treatment can effectively improve the comprehensive road performance of PE modified asphalt.

[0126] 4. Molecular dynamics simulation results show that the absolute value of the binding energy between biomimetic grafted PE and asphalt is significantly increased, and the difference in solubility parameter is significantly reduced. This indicates that biomimetic grafting treatment effectively enhances the interfacial interaction strength between PE and asphalt and improves the thermodynamic compatibility of the two-phase system.

[0127] 5. The dual-interface molecular bridging structure synergistically constructed by PDA and KH550 is a key mechanism for improving the performance of PE-modified asphalt. This structure significantly enhances the interfacial adhesion between PE and asphalt, effectively inhibits PE particle migration and aggregation, and provides molecular-scale theoretical support for the stable dispersion of the modifier in asphalt and the formation of a three-dimensional network structure.

[0128] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing biomimetic grafted polyethylene, characterized in that, Includes the following steps: Polyethylene is oxidized to obtain oxidized polyethylene; The oxidized polyethylene and the dopamine hydrochloride neutralization buffer solution were mixed to produce biomimetic polydopamine biomimetic polyethylene. The biomimetic grafted polyethylene is obtained by mixing the polydopamine biomimetic polyethylene, silane coupling agent and solvent.

2. The preparation method according to claim 1, characterized in that, The mass ratio of the oxidized polyethylene to dopamine hydrochloride is 1:

1.

3. The preparation method according to claim 1, characterized in that, The mass ratio of the polydopamine-inspired polyethylene to the silane coupling agent is 1:

2.

4. The preparation method according to claim 1 or 3, characterized in that, The silane coupling agent includes KH550.

5. The biomimetic grafted polyethylene prepared by the preparation method according to any one of claims 1 to 4.

6. The application of the biomimetic grafted polyethylene as described in claim 5 in the field of asphalt modification.

7. A modified asphalt, characterized in that, It is prepared by sequentially shearing and developing the biomimetic grafted polyethylene and matrix asphalt as described in claim 5.

8. The modified asphalt according to claim 7, characterized in that, The amount of biomimetic grafted polyethylene is 3% to 6% of the mass of the matrix asphalt.

9. The modified asphalt according to claim 7, characterized in that, The shearing parameters include: shearing temperature of 175~185℃, shearing time of 30~60min, and shearing rate of 4000rad / min.

10. The modified asphalt according to claim 7, characterized in that, The development temperature was 165℃ and the time was 30 minutes.